Geological characterization and reservoir evaluation for Mishrif formation in Nasiriyah oilfield - Al-Godi, Saif S.; Al-Obaidi, Dahlia A.; Al-Mudhafar, Watheq J. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Hydrocarbon estimation is a vital step for formation evaluation and development plans, significantly impacting the decision-making process. Well logs data from 40 wells in the Nasiriyah oilfield was utilised to characterise the Mishrif formation and construct a 3D static model. This model illustrates the spatial distribution of petrophysical properties and calculates the Original Oil in Place volume (OOIP) using a volumetric approach. The model incorporates water saturation, effective porosity, permeability, and a 2D structural, which is discretized by 317130 grids. These petrophysical properties are populated in 3D dimensions using the geostatistical method SGS. At the same time, the difference in depths of OWC is captured and represented by three regions of initialization for accurate characterization of the reservoir. The geological modeling identified unit MB1 as the main reservoir in the Mishrif formation, characterized by an average porosity of 21.5%, permeability up to 500 md, and water saturation of 27%. However, unit MB2 exhibits similar petrophysical properties but with significantly higher water saturation above 70%, making it a water-bearing zone. The total OOIP volume for the studied reservoir was calculated to be 8535 MMSTB, mainly accumulated in units MB1 and MB2. Unit MB1 holds approximately 73% of the total oil in place, establishing it as the major reservoir in the Mishrif formation, while unit MB2 contains the remaining 27%.